β-Tocotrienol and δ-Tocotrienol as Additional Inhibitors of the Main Protease of Feline Infectious Peritonitis Virus: An In Silico Analysis - Manos C. Vlasiou; Georgios Nikolaou; Kyriakos Spanoudes; Daphne E. Mavrides (Veterinary Sciences)
Feline infectious peritonitis (FIP) is a severe and invariably fatal disease affecting both domestic and wild felines with limited effective therapeutic options available. By considering the significant immunomodulatory effects of vitamin E observed in both animal and human models under physiological and pathological conditions, we have provided a full in silico investigation of vitamin E and related compounds and their effect on the crystal structure of feline infectious peritonitis virus 3C-like protease (FIPV-3CLpro). This work revealed the β-tocotrienol and δ-tocotrienol analogs as inhibitor candidates for this protein, suggesting their potential as possible drug compounds against FIP or their supplementary use with current medicines against this disease.